ISOLASI DAN KARAKTERISASI BAKTERI RESISTEN CD DARI KAWASAN PENAMBANGAN TIMAH - Septiani, Reti; Lingga, Rahmad; Fabiani, Verry Andre (CONSERVA, 2023)
Bangka Belitung Province is one of the largest tin producing area in Indonesia. One of the mining sites located on the Sampur Beach, Kebintik Village, Central Bangka Regency. Tin mining activities can increase heavy metals harmful to the environment, such as Cadmium (Cd). This research aimed to measure Cd levels in sediment and seawater, to isolate and identify Cd resistant bacteria from sediment. Cd metal was analyzed using Atomic Absorption Spectrophotometer (AAS). The average Cd metal level in seawater is 0,0080 ppm and in sediment is 0,0086 ppm. Bacteria were isolated using Zobell 2216E media with the spread plate method. The isolated Bacteria were tested for resistance to Cd with concentration of 20 ppm, 50 ppm, 80 ppm, 100 ppm, and 120 ppm. From 16 bacterial isolates that have been obtained, 7 isolates were resistant to all concentrations, 1 isolate was resistant to 50 ppm, 1 isolate was only resistant to 20 ppm, and 7 isolates were not resistant. Based on the results of the analyzed, the seven isolates of resistant bacteria have similarity with Halomonas sp. (R2 and R3), Neisseria sp. (R4), Cupriviadus sp. (R5), Bacillus sp. (R11), Alcaligenes sp. (R12), and Roseobacter sp. (R13).